Review on Melting of Multiple Metal Materials in Additive Manufacturing - Andriani, Claudy (2016)
The Additive Manufacturing technologies that are capable of joining dissimilar metals have gained popularity in the past decade because of the advantages they possess over the traditional joining technologies. This paper presents the current state-of-art in laser/electron beam melting of multiple metal materials, specifically through powder bed multi-material processing of metal. The deposition mechanisms discussed are drop-on-demand deposition system and hopper deposition system for laser melting and bottom feeding via a recoater for Electron Beam Melting.